Lauda Sion as Doxological Compendium of St. Thomas’s Eucharistic Theology - Hannon, Urban (New blackfriars, 2024)
In 1264 in the town of Orvieto, St. Thomas Aquinas composed the Lauda Sion as the Mass sequence for Pope Urban IV’s new universal solemnity of the Body and Blood of our Lord Jesus Christ, the feast of Corpus Christi. The present paper will consider this text of St. Thomas’s liturgical sequence in relation to the eucharistic theology that he teaches in the Summa Theologiae. Just as, according to the Dionysian Aquinas, the Psalms contain all the doctrines revealed in the rest of scripture but transposed into the highest literary genre of praise, so the Lauda Sion contains all the essential eucharistic doctrines of the Summa Theologiae, now set in that same laudatory genre as the Psalter. The paper is divided into ten sections, corresponding to the questions in St. Thomas’s treatment of the Holy Eucharist in the Tertia Pars. Proceeding one topic at a time, this paper will show how the Lauda Sion serves as a doxological compendium of St. Thomas Aquinas’s whole eucharistic theology.